The Effectiveness of WDEP (Wants, Doing, Evaluation, Planning) Reality Counseling Model Career Decision-Making Difficulties in Grade XII Students at PGRI Vocational School - Mirza Alnadya; Tatik Meiyuntariningsih (Manunggal Halim Jaya, 2026)
The confusion of the five vocational high school students in determining their career direction is divided into three main categories, namely lack of readiness, lack of information, and inconsistent information. Based on the observation results, the five students showed significant hesitation when asked by the intern about their study and career plans, and did not immediately provide answers when asked directly. This study aims to test the effectiveness of reality counseling using the WDEP (wants, doing, evaluating, planning) model in dealing with career decision-making difficulties of grade XII students of SMK PGRI supported by pre-test and post-test. This research is compiled based on a report presented in the form of a scientific article with participants consisting of five grade XII students of SMK PGRI, identities are disguised to maintain confidentiality and research ethics. The reality counseling intervention of the WDEP (wants, doing, evaluating, planning) model includes an understanding of career decision-making. The results of the study showed that when supported by assessment and intervention, the entire series of assessments (observation, CDMDQ questionnaire, FGD, IST–RMIB–16PF psychological test) and group counseling intervention with a Reality approach (WDEP), it can be concluded that five students (AAF, AM, ARK, FDH, and IPH) experienced difficulties in making career decisions in the high category before the intervention. This obstacle is reflected in low psychological readiness, minimal information about themselves and the career world, and the inconsistency of information from the social environment.